Single metal catalysis: DFT and CAS modelling of species involved in the Fe cation assisted transformation of acetylene to benzene - BLEDA, ERDİ ATA; ALTUN, ZİKRİ (TAYLOR & FRANCIS LTD, 2017)
Gas phase conversion of acetylene to benzene, assisted by a single metal cation such as Fe(+), Ru(+) and Rh(+), offers an attractive prospect for application of computational modelling techniques to catalytic processes. Gas phase processes are not complicated by environmental effects and the participation of a single metal atom is a significant simplification. Still the process is complex, owing to the possibility of several low-energy spin states and the abundance of alternative structures. By density functional theory modelling using recently developed models with range and dispersion corrections, we locate and characterise a number of extreme points on the FeC6H6(+) surface, some of which have not been described previously. These include eta-1, eta-2 and eta-3 complexes of Fe(+) with the C4H4 ring. We identify new FeC6H6(+) structures as well, which may be landmarks for the Fe(+)-catalysed production of benzene from acetylene. The Fe(+) benzene complex is the most stable species on the FeC6H6 cation surface. With the abundant energy of complexation available in the isolated gas phase species, detachment of the Fe(+) and production of benzene can be efficient. We address the issue raised by other investigators whether multi-configurational self-consistent field methods are essential to the proper description of these systems. We find that the relative energy of intrinsically multi-determinant doublets is strongly affected, but judge that the density functional theory (DFT) description provides more accurate estimates of energetics and a more plausible reaction path. [GRAPHICS] .
Keywords: Interconversion of acetylene to benzene; CASSCF; dynamic correlations; MP2; cyclodimerisation; polycyclic system; metallacyclic species; GAS-PHASE; BASIS-SETS; APPROXIMATION; ENERGY; ATOMS